The effects of short- and long-term air pollutants on plant phenology and leaf characteristics. (November 2015) - Jochner, Susanne; Markevych, Iana; Beck, Isabelle; Traidl-Hoffmann, Claudia; Heinrich, Joachim; Menzel, Annette
Abstract: Pollution adversely affects vegetation; however, its impact on phenology and leaf morphology is not satisfactorily understood yet. We analyzed associations between pollutants and phenological data of birch, hazel and horse chestnut in Munich (2010) along with the suitability of leaf morphological parameters of birch for monitoring air pollution using two datasets: cumulated atmospheric concentrations of nitrogen dioxide and ozone derived from passive sampling (short-term exposure) and pollutant information derived from Land Use Regression models (long-term exposure). Partial correlations and stepwise regressions revealed that increased ozone (birch, horse chestnut), NO2, NOx and PM levels (hazel) were significantly related to delays in phenology. Correlations were especially high when rural sites were excluded suggesting a better estimation of long-term within-city pollution. In situ measurements of foliar characteristics of birch were not suitable for bio-monitoring pollution. Inconsistencies between long- and short-term exposure effects suggest some caution when interpreting short-term data collected within field studies. Highlights: We present results of a field survey examining pollution effects on vegetation. Particularly ozone was significantly associated with delays in spring phenology. Leaf morphology of birch was found to be inadequate for bio-monitoring pollution. Inconsistencies between long-/short-term exposure effects suggest caution. Abstract : Pollutants were significantly associated with delays in spring phenology. However, inconsistencies between long- and short-term exposure effects suggest some caution when interpreting results.